Tar Beach - Ringgold, Faith (New York : Crown Publishers, 1991)
A young girl dreams of flying above her Harlem home, claiming all she sees for herself and her family. Based on the author's quilt painting of the same name.
Keywords: African Americans -- Fiction; Flight -- Fiction; Harlem (New York, N.Y.) -- Fiction